Students' Perception Towards The Use of Wordwall in Indonesian Language Learning - Faradisa, Meiliya; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2024)
The use of information and communication technology (ICT)-based learning media in grade VI of SD Negeri 01 Semedo is still limited, although learning media is a crucial factor in the success of the learning process. This study aims to explore students' perceptions of the use of Wordwall application, which provides interactive templates such as images and video games to increase students' interest and engagement in Indonesian language learning. The study involved 23 students as subjects, with data collection conducted through in-depth interviews and focus group discussions (FGDs). The results of the analysis showed that most students gave positive perceptions towards the use of Wordwall, felt more motivated, and actively participated in learning activities. The findings suggest that ICT integration, particularly game-based applications, can enhance students' learning experience as well as better understanding of the material. This study recommends that teachers continue to use technology such as Wordwall in learning to improve student motivation and learning outcomes.